Application of vorticity confinement to rotor wake simulations. (1st January 2012) - Costes, Michel; Renaud, Thomas; Rodriguez, Benoit; Reboul, Gabriel
The VC2 vorticity confinement technique introduced by Steinhoff for vortex dominated flows is presented. After a brief description of the formulation and of its theoretical developments, the method is applied to the simulation of helicopter rotor wakes, focusing on two configurations: the rotor in hover, for which the flow field is mainly driven by the wake characteristics, and the rotor in low-speed descent flight where BVI noise is created. The results obtained show the efficiency of the approach, which provides wake predictions of the same or even better quality as higher-order methods.